Strategic framework for the development of Science Cities an urban enhancement of Science City of Munoz - Cruz, Jennifer A (College of Architecture, University of the Philippines Diliman, 2003)
The development of science cities lies in the realm of community planning. This framework can serve as a tool for greater awareness for future developments of this kind. It can create a systematic and efficient process that will develop science cities and significantly boost advancement and success in the long run. Study, analysis and formulation of adaptive solution in the form of a strategic framework for the identified problem were done.